Needs Expression: A Basic Aspect of Career Behaviour - Harvey, C. Brian; France, M. Honoré (Canadian Journal of Counselling and Psychotherapy, 2011)
This study explores the relationship of anticipated and manifest needs as one method of understanding career behaviour in working nurses (R.N.) and student nurses (B.Sc). The research examines and extends the validity of a manifest and anticipated job-related needs questionnaire in several ways. The data are discussed in terms of the implications for counsellors in helping individuals explore needs both as a factor in vocational choice and as a factor influencing well-being on the job.